The shear behaviors of concrete-gypsum specimens containing double edge cracks under four-point loading conditions. (June 2022) - Fu, Jinwei; Haeri, Hadi; Sarfarazi, Vahab; Asgari, Kaveh; Marji, Mohammad Fatehi
Highlights: The concrete-gypsum specimens are experimentally tested under four-point loading conditions. The influence of edge joint length and joint edge spacing on the tensile behavior of the concrete-gypsum interface are investigated. The same specimens are numerically simulated using the discrite element mehod (DEM). Numerical simulation outputs are in good accordance with experimental test results. Abstract: In this investigation, the fracture behavior of concrete-gypsum samples consisting of edge joints (planer and echelon joints) under four-point bending tests has been investigated using numerical simulation and experimental testing. For this purpose, concrete and gypsum rectangular samples with a dimension of 30 cm * 15 cm * 5 cm have been prepared. These slabs have edge notches in their volume. The lengths of these notches vary by 2 cm in increments of 2 cm, from 2 cm to 6 cm. The slabs were attached with glue. This complex was tested and simulated numerically under four-point loading conditions. The results indicate that the crack growth trajectory is affected by the type of slab material. The strength of samples is controlled by notch length. Numerical simulation outputs are in good accordance with experimental test results.